Diversity of nocturnal Cerambycidae (Coleoptera: Chrysomeloidea) from seven localities in Michoacán, Mexico, with description of a new species - Altamirano, Janeth; Pérez-Flores, Oscar; Escalante-Jiménez, Ana Leticia; Jurado-Vargas, Cesar Marco (Zootaxa, 2024)
We used a long-time light trap for capturing nocturnal beetles. The specimens collected belong to 24 species, 21 genera, 11 tribes, and three subfamilies of the family Cerambycidae. Of these, Gnaphalodes trachyderoides Thomson, 1861; Tylcus hartwegii (White, 1855); Anelaphus piceus (Chemsak, 1962); Metironeus hesperus Chemsak, 1991; Pseudoperiboeum subarmatum Linsley, 1935; Neocompsa puncticollis asperula (Bates, 1885); Compsibidion vanum (Thomson, 1867); Canidia spinicornis (Bates, 1881); Lepturges (Lepturges) angulatus (LeConte, 1852); Sternidius naeviicornis (Bates, 1885); Oreodera noguerai McCarty, 2001; Eupogonius arizonensis Knull, 1954; Lypsimena fuscata Haldeman, 1847; Arhopalus asperatus (LeConte, 1859); and Arhopalus montanus (LeConte, 1873) represent new state records. One new species is described, Adetus michoacanensis sp. nov. (Lamiinae: Apomecynini).